Detection of liver kidney microsomal type 1 antibody using molecularly based immunoassays. Issue 12 (1st December 2002) - Kerkar, N; Ma, Y; Davies, E T; Cheeseman, P; Mieli-Vergani, G; Vergani, D
Abstract : Aims: To assess the diagnostic value of two commercial molecularly based immunoassays detecting liver kidney microsomal type 1 antibody (LKM1). Methods: The performance of Varelisa and LKM1 enzyme linked immunosorbent assay (ELISA) was compared with immunofluorescence, and two validated research techniques—an in house ELISA and a radioligand assay measuring antibodies to P4502D6. Thirty serum samples from three patients with autoimmune hepatitis type 2 covering immunofluorescence titres of 1/10 to 1/10 240 and 55 LKM1 negative controls were tested. Results: All 30 sera that were LKM1 positive by immunofluorescence were positive by the in house ELISA, the radioligand assay, and LKM1-ELISA, and 29 were also positive by Varelisa. None of the 55 sera negative for LKM1 by immunofluorescence was positive by the in house ELISA and radioligand assay, but one was positive by Varelisa and 14 were positive using the LKM1-ELISA. Agreement between immunofluorescence, the in house ELISA, the radioligand assay, and Varelisa was high (κ > 0.8), and agreement between immunofluorescence and LKM1-ELISA was moderate (κ = 0.63). Conclusion: The assay kit marketed as Varelisa allows accurate detection of LKM1.